Respuesta :

[tex]\huge\textsf{Hey there!}[/tex]

[tex]\mathsf{3 - -10 - \dfrac{9}{-1}}[/tex]

[tex]\mathsf{= 3 - (-10) - \dfrac{9}{-1}}[/tex]

[tex]\mathsf{= 3 + 10 - \dfrac{9}{-1}}[/tex]

[tex]\mathsf{3 + 10}\\\\\mathsf{= \bf 13}[/tex]

[tex]\mathsf{= \bold{13} - \dfrac{9}{-1}}[/tex]

[tex]\mathsf{\dfrac{9}{-1}}\\\\\mathsf{= 9\div-1}\\\\\mathsf{= \bf -9}[/tex]

[tex]\mathsf{= 13 - (\bf -9)}[/tex]

[tex]\mathsf{= 13 + 9}[/tex]

[tex]\mathsf{= \bf 22}[/tex]

[tex]\boxed{\boxed{\huge\textsf{Answer: \bf 22}}}\huge\checkmark[/tex]

[tex]\large\textsf{Good luck on your assignment and enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]